# 10th cbse maths solution for exercise 4.1 part 1

## What's new in our website ?

This page 10th cbse maths solution for exercise 4.1 part 1is going to
provide you solution for every problems that you find in the exercise no 2.2

## 10th cbse maths solution for exercise 4.1 part 1

(iii) (x - 2) (x + 1) = (x - 1) (x + 3)

Solution:

x² + 1 x – 2 x - 2 = x² + 3 x - 1 x - 3

x² - 1 x - 2 = x² + 2 x - 3

x² - x²- 1 x - 2 x - 2 + 3 = 0

- 3 x + 1 = 0

This is not exactly matches the general form of quadratic equation. So the given equation is not a quadratic equation.

(iv) (x - 3) (2x + 1) = x (x + 5)

Solution:

2 x² + 1 x – 6 x - 3 = x² + 5 x

2 x² – 5 x - 3 = x² + 5 x

2 x²- x² - 5 x – 5 x - 3 = 0

x² - 10 x - 3 = 0

This exactly matches the general form of quadratic equation. So the given equation is a quadratic equation.

(v) (2 x - 1) (x - 3) = (x + 5) (x - 1)

Solution:

2 x² - 6 x – x + 3 = x² - 1 x - 5 x - 5

2 x² - 7 x + 3 = x² - 6 x - 5

2 x²- x²- 7 x + 6 x + 3 + 5 = 0

x² - 1 x + 8 = 0

This exactly matches the general form of quadratic equation. So the given equation is a quadratic equation.

(vi) x² + 3 x + 1 = (x - 2)²

Solution:

x² + 3 x + 1 = x² - 2 x (2) + 2²

x² + 3 x + 1 = x² - 4 x + 4

x²- x² + 3 x + 4 x + 1 - 4 = 0

7 x - 3 = 0

This is not exactly matches the general form of quadratic equation. So the given equation is not a quadratic equation.

**Related pages**